2016
DOI: 10.1002/uog.15807
|View full text |Cite
|
Sign up to set email alerts
|

Contingent screening for preterm pre-eclampsia

Abstract: Objective Effective screening for pre-eclampsia resulting in delivery < 37 weeks ' gestation (preterm PE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
2
27
1
Order By: Relevance
“…Pulsatility index is the more often and consistently used parameter and its elevated value is an indicator of uteroplacental insufficiency [2529]. Our study showed a trend to decreasing values for 5 and 50 percentiles, but no regular pattern for the 95th.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Pulsatility index is the more often and consistently used parameter and its elevated value is an indicator of uteroplacental insufficiency [2529]. Our study showed a trend to decreasing values for 5 and 50 percentiles, but no regular pattern for the 95th.…”
Section: Discussionmentioning
confidence: 44%
“…The UtA reflects the uteroplacental circulation and it is part of a prediction model for preeclampsia [24, 25]. Pulsatility index is the more often and consistently used parameter and its elevated value is an indicator of uteroplacental insufficiency [2529].…”
Section: Discussionmentioning
confidence: 99%
“…The model was modified in 2016 by proposing that a two-stage prediction process should be performed between 11 and 14 weeks, and between 19 and 24 gestational age, using MAP, UtA-PI and PlGF. Thanks to this modification, detection rates (DR) of 75% and 85% were achieved for the first and second trimesters, respectively; each with a false positive rate (FPR) of 10% [15]. For the purposes of comparison, the model currently proposed by ACOG results in a DR of 90% with an FPR of 67% [16].…”
Section: Current Statusmentioning
confidence: 99%
“…Fourth, the competing‐risks model has been successfully applied for assessment of risk for PE and stratification of pregnancy care by a combination of maternal factors and biomarkers in the first, second and third trimesters of pregnancy. In the first trimester, the competing‐risks approach utilizing maternal factors, MAP, UtA‐PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen‐positive rate, 90% of early‐PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non‐intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively.…”
mentioning
confidence: 99%
“…Consequently, appropriate evaluation and application of biomarkers in screening requires prior standardization by expressing the measured values as multiples of the median (MoM) [28][29][30][31] . In pregnancies that develop PE, MoM values of MAP, UtA-PI and sFlt-1 tend to be higher and PlGF tends to be lower than in normal pregnancies; the effect size increases with increasing severity of the disease, quantified by the gestational age at delivery 5-8 .Fourth, the competing-risks model has been successfully applied for assessment of risk for PE and stratification of pregnancy care by a combination of maternal factors and biomarkers in the first, second and third trimesters of pregnancy [32][33][34][35][36][37][38][39][40][41][42][43][44] . In the first trimester, the competing-risks approach utilizing maternal factors, MAP, UtA-PI and PlGF was used to identify women at high risk of developing preterm PE; at a 10% screen-positive rate, 90% of early-PE cases and 75% of those with preterm PE were predicted in both a training dataset of 35 948 singleton pregnancies and in two independent, non-intervention, multicenter studies involving 8775 and 16 451 singleton pregnancies, respectively 32,[45][46][47][48] .…”
mentioning
confidence: 99%